The Relation Between Academic Procrastination, Symptoms of Attention Deficit Hyperactivity Disorder, and Academic Performance in Medical Students - Sönmez, Özge; Koyuncu, Zehra; Atlı, Zeynep; Hacıkerimoğlu, Özlem; Tekgöl, Nermin Cansu; Kadak, Muhammed Tayyib (Cerrahpaşa Medical Journal, 2023)
Objective: Procrastination is putting off intended tasks that are necessary to reach a goal. Attention deficit hyperactivity disorder (ADHD) is characterized by excessive inattention, impulsivity, and hyperactivity. We aimed to understand the association between academic performance, procrastination, and ADHD. Methods: A group of medical students were screened for procrastination and ADHD by self-report scales. First-, second-, third-, and fourth-year medical students were included in the study. Background information, including birth orders, parents’ education status, department satisfaction, sex, and age, were collected. Tuckman procrastination scale and the adult ADHD self-report scale were applied. Grade point average (GPA) was noted, and it was accepted as an indicator of academic performance. Results: A total of 318 (age: 19.7 ± 1.6; 46% male) volunteer medical students were included. Students with lower GPA had higher tendency to procrastinate than those with high GPA. Even though ADHD self-reported scores were positively correlated with procrastination scores, regression analyses showed that there was no statistically significant association between ADHD symptoms and academic performance. Conclusion: In conclusion, procrastination led to poor academic performance, and nearly half of the students had a tendency to procrastinate. Moreover, students with probable ADHD symptoms tended to procrastinate more. Therefore, students with poor academic performance should be screened for procrastination and ADHD symptoms. Cite this article as: Sönmez Ö, Koyuncu Z, Atlı Z, Hacıkerimoğlu Ö, Tekgöl NC, Kadak MT. The relation between academic procrastination, symptoms of attention deficit hyperactivity disorder, and academic performance in medical students. Cerrahpaşa Med J. 2023;47(3):291-295.